Pelatihan Konseling Multibudaya dalam Pendidikan Konselor - Siti Dwi Yasinta; Disma Nadya Shakila; Rita Munifah Ramadhan; Bakhrudin All Habsy (Edukasi Elita : Jurnal Inovasi Pendidikan, 2025)
Multicultural competence is a crucial aspect for counselors in addressing diverse clients. Multicultural counseling training aims to enhance counselors' understanding of various values, norms, and cultural practices. This research employs a literature review method by collecting, analyzing, and synthesizing various academic sources, including books, research journals, and relevant scientific articles published. The findings indicate that this training helps counselors identify personal biases, improve cross-cultural communication skills, and develop more inclusive intervention strategies. A well-structured multicultural counseling approach can enhance the accessibility and quality of mental health services in diverse communities.